Fast‐swelling oxidized starch phosphate–poly(acrylate/acrylamide/2‐acryloylamino‐2‐methyl‐1‐propanesulfonic acid) superabsorbent composite. Issue 11 (3rd June 2016) - Qi, Xiaohua; Liu, Mingzhu; Chen, Zhenbin
Abstract : A fast‐swelling superabsorbent composite was prepared by solution polymerization of acrylate, acrylamide, 2‐acryloylamino‐2‐methyl‐1‐propanesulfonic acid and oxidized starch phosphate. Ethanol, propyl alcohol, butyl alcohol, and sodium bicarbonate were used as foaming agents to produce fast‐swelling characteristics. The structure of the superabsorbent composite was characterized using Fourier transform infrared spectroscopy (FTIR). The influences of the amount of water, acrylamide, 2‐acryloylamino‐2‐methyl‐1‐propanesulfonic acid, oxidized starch phosphate, initiator, and trihydroxymethyl propane glycidol ether, as well as the neutralization degree of acrylic acid on the equilibrium swelling degree and swelling rate of the superabsorbent composite, were investigated. The equilibrium swelling degree of the superabsorbent composite prepared in a 0.9 wt% NaCl aqueous solution was 52 g g −1, and the swelling rate reached 0.86 mL g −1 s −1 . The swelling kinetics was also investigated, and the results indicate that swelling of the superabsorbent composites obeys Schott's pseudo second‐order kinetics model. POLYM. ENG. SCI., 56:1267–1274, 2016. © 2016 Society of Plastics Engineers